2017
DOI: 10.1080/09638237.2017.1385739
|View full text |Cite
|
Sign up to set email alerts
|

Describing the profile of a population of UK veterans seeking support for mental health difficulties

Abstract: Results indicate the complexity of presentations within treatment seeking veterans. These difficulties may partly explain the poorer treatment outcomes reported in veterans in comparison to the general public. As such, it would be prudent for interventions targeted at veterans with mental health difficulties to attempt to address the range of issues faced by this population rather than focus on a particular presenting problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
89
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 32 publications
9
89
2
Order By: Relevance
“…In addition to PTSD, 90.4% of participants met case criteria for depression, 94.6% for generalized anxiety, 50.8% for problems with anger, and 45.5% for alcohol problems. These were broadly in line with the characteristics of the wider population of individuals who seek support from Combat Stress (Murphy, Ashwick, Palmer, & Busuttil, ). However, of this wider population, only individuals who met the inclusion and exclusion criteria were referred for treatment on the 6‐week treatment program for PTSD, and bed space was limited to approximately 300 participants per year.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…In addition to PTSD, 90.4% of participants met case criteria for depression, 94.6% for generalized anxiety, 50.8% for problems with anger, and 45.5% for alcohol problems. These were broadly in line with the characteristics of the wider population of individuals who seek support from Combat Stress (Murphy, Ashwick, Palmer, & Busuttil, ). However, of this wider population, only individuals who met the inclusion and exclusion criteria were referred for treatment on the 6‐week treatment program for PTSD, and bed space was limited to approximately 300 participants per year.…”
Section: Resultssupporting
confidence: 74%
“…Authors of previous research have shown the most serious presentations of PTSD in veterans in the United Kingdom are associated with higher levels of comorbid mental health difficulties, substance misuse, childhood adversity, and not being in a relationship, all of which may be indicative of more complex presentations (Murphy et al., ). The 11th revision of the International Classification of Diseases ( ICD‐11 ; World Health Organization, ) was published in 2018 and includes a diagnosis of complex PTSD; it seems prudent to explore this diagnosis within veteran populations.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the current sample may differ from veterans who seek treatment from other services. For example, the majority of veterans seeking treatment from Combat Stress present with PTSD and comorbid difficulties such as common mental health problems and alcohol misuse 14. On the other hand, common mental health difficulties are the most prevalent conditions in veterans in general 1.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 403 out of 600 individuals returned completed questionnaires. There were no differences between those who participated in the study and those who did not, as shown by published data 13. These data were then linked using a unique patient identification number to risk assessment data contained within patients’ electronic files.…”
Section: Methodsmentioning
confidence: 99%